ANALISIS FAKTOR-FAKTOR YANG MENDORONG WAJIB PAJAK RESTORAN DALAM MELAPORKAN KEWAJIBAN PERPAJAKANNYA DI KOTA MANADO - Pantow, Yunika Handayani; Karamoy, Herman; Pangerapan, Sonny (Universitas Sam Ratulangi, 2020)
Based on Local Regulation No. 2 of 2011 concerning Regional Taxes which states the procedure for setting tax rates, the procedure for collecting and paying Restaurant Tax in the City of Manado. Taxpayers are given the authority and trust to be able to calculate, pay and report their own tax amounts. This study aims to determine whether taxpayer knowledge can encourage awareness in fulfilling tax obligations in the city of Manado and what factors prevent taxpayers from fulfilling their obligations. The method used in this research is descriptive qualitative analysis. The results of this study indicate that restaurant taxpayers in the city of Manado in terms of knowing the tax regulations that apply to restaurant taxes and calculating the amount of tax to be paid in accordance with the rules of 15 speakers, paying 13 speakers, reporting 11 speakers. The Manado City BP2RD must work closely with the government in conducting socialization/counseling about collecting restaurant taxes and installing more strategic tax slogans.